RISÄ€LAH MENURUT KONSEPSI ALQURAN - Mukhtar, Mukhlis (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: The word al-risÄlah is one of the words used in the Qurâ€™an. The existence of al-risÄlah cannot be separated from the presence of the messenger of AllahÂ  among mankind in every age.Â  That is because the messengers were given the recommendation directly by God to carry, to deliver and to Â teach al-risÄlah.Â  Al-risÄlah carried, delivered and taught by the messengers to mankind contains the messages of the Almighty God Â to invite people not to worship God except Â Allah and regulate human life in relation to God, fellow humans and their environment. Kata Kunci: Â risalah, kosepsi Alquran, rasul